Safety, efficacy and glucose turnover of reduced prandial boluses during closed‐loop therapy in adolescents with type 1 diabetes: a randomized clinical trial. Issue 12 (9th October 2015) - Elleri, D.; Biagioni, M.; Allen, J. M.; Kumareswaran, K.; Leelarathna, L.; Caldwell, K.; Nodale, M.; Wilinska, M. E.; Haidar, A.; Calhoun, P.; Kollman, C.; Jackson, N. C.; et al.
Abstract : Aims: To evaluate safety, efficacy and glucose turnover during closed‐loop with meal announcement using reduced prandial insulin boluses in adolescents with type 1 diabetes (T1D). Methods: We conducted a randomized crossover study comparing closed‐loop therapy with standard prandial insulin boluses versus closed‐loop therapy with prandial boluses reduced by 25%. Eight adolescents with T1D [3 males; mean (standard deviation) age 15.9 (1.5) years, glycated haemoglobin 74 (17) mmol/mol; median (interquartile range) total daily dose 0.9 (0.7, 1.1) IU/kg/day] were studied on two 36‐h‐long visits. In random order, subjects received closed‐loop therapy with either standard or reduced insulin boluses administered with main meals (50–80 g carbohydrates) but not with snacks (15–30 g carbohydrates). Stable‐label tracer dilution methodology measured total glucose appearance (Ra_total) and glucose disposal (Rd). Results: The median (interquartile range) time spent in target (3.9–10 mmol/l) was similar between the two interventions [74 (66, 84)% vs 80 (65, 96)%; p = 0.87] as was time spent above 10 mmol/l [21.8 (16.3, 33.5)% vs 18.0 (4.1, 34.2)%; p = 0.87] and below 3.9 mmol/l [0 (0, 1.5)% vs 0 (0, 1.8)%; p = 0.88]. Mean plasma glucose was identical during the two interventions [8.4 (0.9) mmol/l; p = 0.98]. Hypoglycaemia occurred once 1.5 h post‐meal during closed‐loop therapy with standard bolus. Overall insulin delivery was lower with reduced prandial boluses [61.9 (55.2, 75.0) vs 72.5 (63.6, 80.3) IU; p = 0.01] and resulted in lower mean plasma insulin concentration [186 (171, 260) vs 252 (198, 336) pmol/l; p = 0.002]. Lower plasma insulin was also documented overnight [160 (136, 192) vs 191 (133, 252) pmol/l; p = 0.01, pooled nights]. Ra_total was similar [26.3 (21.9, 28.0) vs 25.4 (21.0, 29.2) µmol/kg/min; p = 0.19] during the two interventions as was Rd [25.8 (21.0, 26.9) vs 25.2 (21.2, 28.8) µmol/kg/min; p = 0.46]. Conclusions: A 25% reduction in prandial boluses during closed‐loop therapy maintains similar glucose control in adolescents with T1D whilst lowering overall plasma insulin levels. It remains unclear whether closed‐loop therapy with a 25% reduction in prandial boluses would prevent postprandial hypoglycaemia.